1994
DOI: 10.1111/j.1432-1033.1994.tb18931.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant plant cinnamate 4‐hydroxylase produced in yeast

Abstract: Helianthus tuberosus cinnamate 4-hydroxylase (CYP73 or CA4H), a member of the P450 superfamily which catalyses the first oxidative step of the phenylpropanoid pathway in higher plants by transforming cinnamate into p-coumarate, was expressed in the yeast Succharomyces cerevisiae. The PCR-amplified CA4H open reading frame was inserted into pYeDP60 under the transcriptional control of a galactose-inducible artificial promoter. Engineered S. cerevisk strains producing human P450 reductase or normal or overproduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 35 publications
8
118
1
Order By: Relevance
“…CYP73A1 content was quantified by differential spectrophotometry (presence versus absence of saturating concentration of substrate) using an absorption coefficient ( E ) for the A,,, to A,,, difference of 128 mM-' (Urban et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…CYP73A1 content was quantified by differential spectrophotometry (presence versus absence of saturating concentration of substrate) using an absorption coefficient ( E ) for the A,,, to A,,, difference of 128 mM-' (Urban et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…[17]), and by the finding that a plant P45o-RED was able to support reactions of animal P450 [19]. It has also been shown that yeast reductase interacted successfully with plant P450 [4,7,36].…”
Section: Discussionmentioning
confidence: 95%
“…Expression of functionally identified plant P450 in other cells has been reported (e.g. yeast [4,7] and animal cells [8,9]), but each of the available systems suffer from certain limitations including ease of use or expense.…”
Section: Introductionmentioning
confidence: 99%
“…The turnover number (k cat ) and the catalytic efficiency (k cat /K m ) with 3-hydroxy-5-methoxybiphenyl were 0.342 min 21 and 2,375 M 21 s 21 , respectively (Table II). When SaCPR was incubated with cytochrome c as an artificial electron acceptor (Urban et al, 1994), the K m value for NADPH was 51 6 5.4 mM. No appreciable loss of SaB4H activity was observed upon storage of microsomal preparations in Tris-EDTA-glycerol buffer at 280°C for 6 months.…”
Section: Functional Characterization Of Cyp736a107mentioning
confidence: 99%
“…The CPR assay (1 mL) contained 40 mM cytochrome c (equine heart; SigmaAldrich; www.sigmaaldrich.com), 0.1 mM EDTA, and 12 mg of microsomal fraction in 0.1 M potassium phosphate buffer, pH 7.5 (Urban et al, 1990(Urban et al, , 1994. The reaction was started by the addition of NADPH.…”
Section: Enzyme Assaysmentioning
confidence: 99%